The Influence of Microstructure on the Corrosion Rate of Carbon Steels - Sami I. Al-rubaiey; Eman A. Anoon; Mahdi M. Hanoon (Engineering and Technology Journal, 2013)
This paper presents the influence of carbon steel microstructure on the corrosion rates. Four types of microstructures have obtained by quenching and tempering and iso-thermal annealing. These microstructures are: banded ferrite/pearlite microstructure, fine ferrite/pearlite microstructure, coarse ferrite/pearlite microstructure and tempered martensite microstructure. General corrosion and localized corrosion (penetration rates) were determined via mass loss and optical microscopy. The different microstructures of steels investigated in this paper revealed corrosion rate variations of 0.8– 3.2 mm y-1 and 3.3–6.4 - mm y-1 for the general and localized forms, respectively. The corrosion stability of the various microstructures may arise from variations of phases within the steel. A banded ferrite/pearlite microstructures have worse general corrosion properties, while tempered martensite worse microstructures have localized pitting corrosion properties. Coarse ferrite/pearlite microstructures have better localized pitting corrosion resistances compared to others investigated microstructures This paper has demonstrated that, microstructure is an important consideration when selecting carbon steel for an industrial corrosion resistance application.